Utilization of Learning Game Kahoot to Improve Students Preparedness in Facing Disasters Forest and Land Fires at SMAN 1 Rantau Badauh - Yanuardi, Arendra; Arisanty, Deasy; Muhaimin, Muhammad; Alviawati, Eva; Saputra, Aswin Nur (Universitas Lambung Mangkurat, 2025)
The application of learning using the kahoot game media can be applied to improve student learning outcomes. This research is aimed at finding out the effect of using the Kahoot learning game media on student learning outcomes. The population of this research is class XII IPS 2 students at SMAN 1 Rantau Badauh, with a total of 22 students. The research carried out is included in the type of experimental research. The method in this research is Pre-Experimental Design (Pre-Experimental Design) using a quantitative approach with a series of One-Group Pretest-Posttest research. The results of the research using the N-Gain test are an average value of 56.4989 or 56%, which is quite effective and according to the N-Gain category is moderate. Based on the hypothesis using a paired difference test (Paired Sample t-Test) it is known that the Sig value. (2-tailed) is 0.000 < 0.05, so H0 is rejected and H1 is accepted. So the conclusion is that there is a difference in the average of pretest and posttest learning outcomes, meaning that there is an influence on the use of the Kahoot learning game media on student learning outcomes to increase preparedness in facing forest and land fire disasters in class XII IPS 2 at SMAN 1 Rantau Badauh.